Full up? (Economist, 2000)
Discusses a proposal by German Chancellor Gerhard Schroder to give temporary work permits to Indians and East Europeans in an effort to meet Germany's need for computer specialists. Numbers of immigrants as of 2000, and responses to the policy proposal; Departure of foreigners; Demographic transition; Impact of the expansion of the European Union.